2020
DOI: 10.4314/sajas.v50i3.1
|View full text |Cite
|
Sign up to set email alerts
|

Association of polymorphisms of vasoactive intestinal peptide and its receptor with reproductive traits of turkey hens

Abstract: The aim of this study was to identify variations of vasoactive intestinal peptide (VIP) and VIP receptor-1 (VIPR-1) genes that might be associated with turkey reproductive traits. One hundred twenty turkey hens were recorded for age at first egg (AFE), first egg weight (FEW), egg number (EN), total egg weight (TEW), laying period (LP), and broodiness. The DNA was isolated from blood samples and subjected to PCR amplification of the meleagrine VIP and VIPR-1 genes. The SNPs were detected by single-strand confor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“… Zhou et al (2008) have shown that 7 sites (A-284G, A+457G, C+598T, D+19820I, C+37454T, C+42913T, and C+53327T) of VIPR-1 gene might be associated with broodiness. Hosseinpour et al (2020) have shown that 2 SNPs (C17687T and A17690T) of VIPR-1 gene were associated with egg production traits, egg number, total egg weight, and laying period in turkey hens. The present study was conducted to determine if the polymorphisms of the VIPR-1 gene were correlated with the growth traits at 3 and 5 wk of age in quails ( Figure 4 ).…”
Section: Results and Disscusionmentioning
confidence: 99%
“… Zhou et al (2008) have shown that 7 sites (A-284G, A+457G, C+598T, D+19820I, C+37454T, C+42913T, and C+53327T) of VIPR-1 gene might be associated with broodiness. Hosseinpour et al (2020) have shown that 2 SNPs (C17687T and A17690T) of VIPR-1 gene were associated with egg production traits, egg number, total egg weight, and laying period in turkey hens. The present study was conducted to determine if the polymorphisms of the VIPR-1 gene were correlated with the growth traits at 3 and 5 wk of age in quails ( Figure 4 ).…”
Section: Results and Disscusionmentioning
confidence: 99%
“…VIP binds to the N-terminal end of the receptor, which in turbot contains an Asn2Gln polymorphism. VIPR1 polymorphism has been linked to gastrointestinal dysmotility disorders in man 120 , but associated with reproductive traits in birds 121 . Two polymorphic hepcidins have been identified in turbot 122 of which hep1 was highly polymorphic in all populations and farms examined, particularly in the Black Sea and farm 3.…”
Section: Discussionmentioning
confidence: 99%